Bioluminescence imaging to track bacterial dissemination of Yersinia pestis using different routes of infection in mice - Gonzalez, Rodrigo J (BioMed Central, 2012)
BACKGROUND: Plague is caused by Yersinia pestis, a bacterium that disseminates inside of the host at remarkably high rates. Plague bacilli disrupt normal immune responses in the host allowing for systematic spread that is fatal if left untreated. How Y. pestis disseminates from the site of infection to deeper tissues is unknown. Dissemination studies for plague are typically performed in mice by determining the bacterial burden in specific organs at various time points. To follow bacterial dissemination during plague infections in mice we tested the possibility of using bioluminescence imaging (BLI), an alternative non-invasive approach. Fully virulent Y. pestis was transformed with a plasmid containing the luxCDABE genes, making it able to produce light; this lux-expressing strain was used to infect mice by subcutaneous, intradermal or intranasal inoculation. RESULTS: We successfully obtained images from infected animals and were able to follow bacterial dissemination over time for each of the three different routes of inoculation. We also compared the radiance signal from animals infected with a wild type strain and a Δcaf1ΔpsaA mutant that we previously showed to be attenuated in colonization of the lymph node and systemic dissemination. Radiance signals from mice infected with the wild type strain were larger than values obtained from mice infected with the mutant strain (linear regression of normalized values, P < 0.05). CONCLUSIONS: We demonstrate that BLI is useful for monitoring dissemination from multiple inoculation sites, and for characterization of mutants with defects in colonization or dissemination.